MODEL PERILAKU PENGGUNAAN TIK “NR2007” PENGEMBANGAN DARI TECHNOLOGY ACCEPTANCE MODEL (TAM) - Neila Ramdhani (Buletin Psikologi, 2009)
This paper discusses and criticizes a Technology Acceptance Model which was developed by Fred D. Davis in 1986. TAM was built to predict the way people accept and adopt the technology. TAM was inspired by theory of reasoned action (TRA) formulated by Martin Fishbein & Icek Ajzen in 1975, although the model does not completely adopt the TRA model. TAM does not include Subjective Norm as a factor in predicting the use of technology. As a theory, TAM has been used by many researchers to investigate the adoption of information technology. This model has a significant contribution in predicting the use of information communication technology (ICT) in many areas. Since ICT users have various motivational backgrounds, some of them have a positive attitude toward ICT, but they do not use ICT. It seems the TAM model need to be improved by including Subjective Norms and Perceived Behavior Control as suggested by Ajzen in the theory of planned behavior (TPB) as antecedents of intention to use ICT. Since the personality background of ICT users may also influence the use of ICT, the author proposes TAM‐NR‐2007 model that include personality traits as a background factor of attitude toward the behavior and subjective norms.